Environmental spatial mapping within equine indoor arenas - McGill, Staci; Coleman, Robert; Jackson, Josh; Tumlin, Kimberly; Stanton, Victoria; Hayes, Morgan (Frontiers in Animal Science, 2023)
Equine indoor arenas are unique infrastructure investments found at equine farms and facilities. Environmental concerns within these facilities (temperature, respirable dust, moisture, and air movement) have been identified through surveys and small research studies. Thirty-seven indoor arenas at equine facilities within 160 km (100 miles) of Lexington, KY, were visited from August 2018 to August 2021. Semi-structured interviews were conducted to gather more information regarding the environment within the indoor arena and information about the equine facility. Site assessments were also conducted and temperatures (footing or ground level, air at 1.37 m above the footing, and roof), air speeds at 1.37 m above the footing, and light levels at 1.37 m above the footing across the indoor arena spaces were measured, in addition to the total number of horses at the facilities and daily average and maximum use of the indoor arenas. Spatial mapping was conducted using ArcMap 10.7 (Esri; Redlands, California), with kriging being used for the interpolation. The created maps were used to determine the variability of the temperatures, air speed, and lighting within the indoor arenas. These variabilities were examined for the statistical significance for variables of the indoor arenas that were determined by structural and design aspects and for facility usage information gathered from the semi-structured interviews. The variables that were statistically significant were roof ventilation for roof temperature variability, roof insulation for footing temperature variability, building enclosure for lighting variability, total number of horses at the facility for lighting variability, and total daily number of horses in the indoor arena for the ambient air temperature variability. One of the most significant results was the lack of air movement observed in the majority of the indoor arenas. Over 80% of the indoor arenas were experiencing still air speed conditions (< 0.51 m/s) during the site assessment. There is a need for more research on the environmental conditions within indoor arenas, the potential health impacts to the humans and horses in the spaces, and how design changes to the facilities could improve these environments.